Solve the problem of three-dimensional transportation using multi-objective programming - Abdul - Jabbar Khudr Bakhit; Suhad Faisal Aboud (Journal of Madenat Alelem University College, 2018)
The problem of transportation is one of the most important mathematical methods that help in making the appropriate decision to move goods from the sources of processing to the centers of demand and With lowest possible costs, in the research was based on the mathematical model of the problem of three-dimensional transportation where the transport of sales is not homogenous, Fuzzy Multi-objective programming method to solving the problem of transporting food products (sugar, oil, rice) from the warehouses to the demand areas in Baghdad and also used two types of membership functions, linear and exponential. The results showed that the linearity function was better than the exponential affinity function in reducing the total transportation costs of (6,850,707.4) million dinars, and reducing the total transportation time of (412,623.26) hours